THE ROLE OF THE FINANCIAL SERVICES AUTHORITY IN PROTECTING CRYPTO ASSET INVESTORS IN INDONESIA: BETWEEN REGULATION AND SUPERVISION - Sri Rokhmawati; Upik Mutiara; Rizki Zulva Pratama; Indra Effendi; Septian Ibrohim (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
The number of investors has reached tens of millions, with transaction values amounting to hundreds of trillions of rupiah annually. This phenomenon presents significant digital economic potential while simultaneously posing high risks to investors due to price volatility, weak legal protection, and the widespread occurrence of fraud and hacking practices. With the enactment of Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law), the authority for supervising crypto assets was transferred from Bappebti to the Financial Services Authority (OJK). This study aims to analyze the role of OJK in providing legal protection for crypto asset investors through regulatory and supervisory approaches. The research employs a normative legal research method by examining statutory regulations, academic literature, and relevant OJK policies. The findings indicate that this transfer of authority constitutes a strategic step toward strengthening crypto asset governance; however, it still faces challenges in the form of legal gaps, overlapping institutional authorities, and limited technical supervisory capacity due to the decentralized nature of crypto assets. OJK is therefore required to accelerate the formulation of technical regulations, strengthen coordination with related institutions, develop blockchain analytics–based supervisory technologies, and enhance public digital financial literacy. In conclusion, the effectiveness of OJK’s role in protecting crypto asset investors largely depends on its ability to adapt to digital innovation and to establish a responsive, collaborative, and evidence-based regulatory system.